Customs management in multinational companies - Grainger, Andrew (Centre for Customs and Excise Studies (CCES), Charles Sturt University, Australia, 2016)
What do senior customs managers within multinational companies do? By answering this seemingly simple question this paper sheds light on an overlooked but significant business function with immediate relevance to logistics and supply chain management practice. The paper draws on a series of long interviews with key informants at nine multinational companies. Their combined annual turnover is in excess of $400 billion. Multiple feedback cycles enabled robust analysis and factual accuracy. A review of relevant customs law, procedures and literature gives the necessary context. Findings show that senior customs managers are involved in three interdependent areas of activity: logistics support, supply chain management and regulatory compliance. However, there is considerable diversity in practice and managers are often drawn between allocating time and effort to reducing costs, safeguarding compliance and developing strategic capabilities. The identified customs management practices provide an opportunity for relevant staff in companies to identify and reflect on scope for improvements and to take more informed trade-off decisions about the allocated time and effort. A more informed understanding of the customs management practices also has utility for trade and customs policy makers tasked with reducing the transaction costs between businesses and border agencies—especially in the context of trade facilitation. Last, but not least, the paper may also serve as a stepping stone for further academic enquiry that extends the link between businesses and Customs agencies.